From Red-Light Districts to Public Spaces: Collaborative Governance and Social Innovation in Burnik City, Situbondo - Widiyatmoko, Faris; Fatta, Nurul; Asmuni (Universitas Wijaya Kusuma Surabaya, 2026)
The transformation of former red-light districts into public spaces presents a complex policy challenge because it involves social, economic, and moral dimensions. This article analyzes collaborative governance and social innovation in the transformation of Burnik City in Situbondo Regency using a qualitative approach through interviews, observations, and document analysis. The research findings indicate that cross-actor collaboration functions as a social infrastructure enabling spatial change; however, this collaboration does not occur on equal terms due to the influence of power relations and the roles of key actors. This transformation yields social innovation across three dimensions: meeting social needs, transforming social relations, and community empowerment. Although it has succeeded in shifting stigma and boosting economic activity, the resulting innovations remain partial as they have not yet been strongly institutionalized. Furthermore, spatial transformation also has the potential to create new forms of exclusion for certain groups. Sustainability challenges related to institutional frameworks, participation, and the environment highlight the need for institutional strengthening to ensure that social innovations can endure in the long term.